5-fluorouracil adsorption on hydrated silica: density functional theory based-study - Díaz Compañy, Andrés Carlos Daniel (2017)
Hydrated SiO2(111) has been projected as a competent support of an anticancer drug, 5-fluorouracil (5-FU). Theoretical calculations using the Vienna Ab-initio Simulation Package (VASP) were performed to study the drug-silica interactions that control the adsorption of 5-fluorouracil (5-FU) on an hydrated SiO2(111) surface. Only dispersive interactions are presented during the drug adsorption on the hydrophobic surface while cooperation exists between directional H-bonds and dispersion forces on hydrated silica. H-bonds become dominant for the hydrophilic surface driven interactions with important energetic consequences on adsorption. The density of states slightly shifted towards lower energy values showing a stabilization of the electron states of the 5-FU molecule on hydrated silica, and the electronic charge transfer mainly happens on the interface between polar groups of 5-FU and the nearest silanol groups, in agreement with the formation of the H-bonding interactions. The results reveal the remarkable influence of H-bonds in the adsorption mechanism on hydrated silica.